2017
DOI: 10.1007/s00261-017-1158-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of supradiaphragmatic lymph nodes at initial presentation in patients with stage III high-grade serous ovarian cancer

Abstract: In patients with stage III HGSC, supradiaphragmatic lymphadenopathy is associated with shorter PFS and OS. Further studies would help determine its implications on staging, decision regarding neoadjuvant therapy, and surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Thirteen articles described retrospective cohort studies [ 9 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], one was a case report [ 34 ], and one a case series [ 35 ]. The studies spanned the period from 1997 to 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles described retrospective cohort studies [ 9 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], one was a case report [ 34 ], and one a case series [ 35 ]. The studies spanned the period from 1997 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this finding, only a slightly higher proportion of perioperative complications was found for the CPLN adenopathy group (26% vs. 23%). Eight studies provided survival outcomes [ 9 , 11 , 24 , 25 , 26 , 29 , 32 , 33 ]. The pooled median PFS time was 14.6 months (95% CI 4.9–24.4) vs. 27.8 months (95% CI 3.2–52.5) in patients with and without CPLN adenopathy, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, Kurtin et al (29) reported that lymph node involvement was not associated with an adverse outcome in patients with pulmonary MALT lymphoma. The prognostic role of regional LAP in several malignancies has been considered in previous studies (30,31) and reviews (32). Cahoon et al (32) indicated that understaging of internal thoracic LAP in patients with breast cancer significantly impacted patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Celiac lymph node involvement is accompanied with higher rates of large bowel resection and higher incidence of metastasis to small bowel mesentery (44). Lymph node involvement in general does not seem to favorite primary cytoreductive surgery, while peritoneal carcinomatosis increases the rates of cytoreductive failure and surgical complications, if upfront debulking surgery is decided (10,45,46).…”
Section: Peritoneal Carcinomatosismentioning
confidence: 99%
“…Video-assisted thoracoscopy (VATS) was suggested as optimal imaging technique in patients with pleural involvement, in order to assess the stage of the disease, whereas real-time ultrasound elastography was able to evaluate chemotherapy response but the application of the technique is quite limited (3,24). Furthermore, diffusion weighted MRI (DW-MRI) offers an estimated superior predictive value for cytoreductive outcome in approximately 90% of the cases, providing essential information on serosal intestinal, mesenteric vascular and distant site involvement (3,24,46). Last but not least, sonography has been evolved over the years, and although its use is limited, adequate pre-operative assessment of the extent of the disease can be achieved.…”
Section: Radiographic and Nuclear Imagingmentioning
confidence: 99%